If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-4Z + -5) = 0 Reorder the terms: -3(-5 + -4Z) = 0 (-5 * -3 + -4Z * -3) = 0 (15 + 12Z) = 0 Solving 15 + 12Z = 0 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 12Z = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 12Z = 0 + -15 12Z = 0 + -15 Combine like terms: 0 + -15 = -15 12Z = -15 Divide each side by '12'. Z = -1.25 Simplifying Z = -1.25
| x=45+12x | | (2a+3)(3a-4)= | | 9=4+5x | | 75-x=x+5 | | 0.25+2x=360 | | 5y+9-y=26 | | 0.9(7x+4)=0.7-(x-3) | | 10t-6-t=9t-6 | | -10+10+-5B*2+-1+-5B= | | 4x-2+x=-2+2 | | 3(3x-8)=4x-6 | | 51x+18-29x=131 | | 8a-(1+5a)=4(3a-11)-24 | | 11b+4=37 | | 11x+8+17x-17=13x+79 | | m=m(c)2 | | 3m-1-6=13+7m | | w+2=-43-8t | | 28b^2-80b-12= | | 4x+35-15=9x-45 | | 3n+8=57 | | 1.8x+1.2x-5.4=-10 | | 2w(4w-1)=w(1-4w) | | 3(2x-1)=9x+3 | | 1a=-5a | | 0.08(x-100)=83.5-0.07 | | 3n+4=57 | | 5y+10-y=29 | | f(x)=x^2-4x-44 | | -8(v+7)+8=-33-5v | | Y+5-9=10 | | 2=2.27-4 |